Development of Orodispersible Tablets with Solid Dispersions of Fenofibrate and Co-Processed Mesoporous Silica for Improved Dissolution - Ana Baumgartner; Odon Planinšek (MDPI AG, 2024)
Poor water solubility is an important challenge in the development of oral patient-friendly solid dosage forms. This study aimed to prepare orodispersible tablets with solid dispersions of a poorly water-soluble drug fenofibrate and a co-processed excipient consisting of mesoporous silica and isomalt. This co-processed excipient, developed in a previous study, exhibited improved flow and compression properties compared to pure silica while maintaining a high specific surface area for drug adsorption. Rotary evaporation was used to formulate solid dispersions with different amounts of fenofibrate, which were evaluated for solid state properties and drug release. The solid dispersion with 30% fenofibrate showed no signs of crystallinity and had a significantly improved dissolution rate, making it the optimal sample for formulation or orodispersible tablets. The aim was to produce tablets with minimal amounts of additional excipients while achieving a drug release profile similar to the uncompressed solid dispersion. The compressed formulations met the requirements for orodispersible tablets in terms of disintegration time, and the drug release from best formulation approximated the profile of uncompressed solid dispersion. Future research should focus on reducing the disintegration time and tablet size to enhance patient acceptability further.